Prognostic Value of Global Longitudinal Strain in Asymptomatic Aortic Stenosis: A Systematic Review and Meta-Analysis - Wang, Yuan; Zhang, Minghui; Chen, Hui; Li, Hongwei (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds: The presence of impaired GLS may be a valuable bio-marker in the early diagnosis for left ventricle (LV) impairment, which would help scrutinize asymptomatic aortic stenosis (AS) patients with high risk of adverse outcomes including major adverse cardiovascular events (MACE). Methods: The study was prospectively registered in PROPSERO (CRD 42021223472). Databases including Pubmed, Embase, Cochrane Library, Web of science, and Scopus were searched for studies evaluating the impact of impaired GLS on MACE, all-cause mortality, and aortic valve replacement (AVR) in asymptomatic AS. Hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated with meta-analysis for binary variants. Meta-regression, subgroup analysis and sensitivity analyses were applied as needed to explore the heterogeneity. Results: Eventually, a total of 9 studies reporting 1512 patients were enrolled. Compared with normal GLS group, impaired GLS significantly increased MACE (HR = 1.20, 95%CI: 1.10 to 1.30, I2 = 79%) with evident heterogeneity, all-cause mortality (HR = 1.42, 95%CI: 1.24 to 1.63), and AVR (HR = 1.17, 95%CI: 1.07 to 1.28). Subgroup analyses stratified by LVEF >50% or LVEF without precise cut-off point found that compared with normal GLS group, impaired GLS remarkably increased MACE both in two subgroups (LVEF>50%: HR: 1.22, 95%CI: 1.05 to 1.50; LVEF without cutpoint: HR: 1.25, 95%CI: 1.05 to 1.50). The results stratified by AS severity (mild/moderate and severe) or follow-up time resembled those stratified by LVEF. In addition, when subgroup analysis was stratified by mean aortic valve pressure gradient (MG ≥40 mmHg and MG<40 mmHg), compared with normal GLS, impaired GLS significantly increased MACE both in two subgroups (MG ≥40 mmHg: HR: 3.41, 95%CI: 1.64 to 7.09; MG below 40 mmHg: HR: 3.17, 95%CI: 1.87 to 5.38). Moreover the effect sizes here were substantially higher than those in the former two stratified factors. Conclusions: The presence of impaired GLS substantially worsens the outcomes for adverse cardiovascular events in asymptomatic AS patients regardless of LVEF or AS severity or follow-up time or mean aortic valve pressure gradient, which highlights the importance of incorporating impaired GLS into risk algorithms in asymptomatic AS.